Illustrate the metabolic regulatory effects of Ganoderma Lucidum polysaccharides on cognitive dysfunction in formaldehyde-exposed mouse brain by mass spectrometry imaging - Wen Wang; Yuanyuan Sun; Renting Cao; Wenhui Luo; Shujuan Beng; Jing Zhang; Xiaoqun Wang; Can Peng (Ecotoxicology and Environmental Safety)
Long-term formaldehyde (FA) exposure causes cognitive dysfunction, often associated with metabolic disorders. While some studies suggest Ganoderma lucidum polysaccharides (GLP) can improve cognitive function, such as Alzheimer's disease. However, the effects of GLP on FA-exposed cognitive dysfunction and the regulation of GLP on brain metabolic disturbances caused by FA remain unclear. In our study, we revealed that GLP significantly reversed FA-exposed spatial cognitive deficits in mice by using Morris Water Maze and Histological analysis. Furthermore, desorption electrospray ionization mass spectrometry imaging (DESI-MSI) found that exposure of FA can caused dysregulated expression of 35 metabolites. Following GLP treatment, there was a significant restoration of the imbalance of choline and acetylcholine, carnitine and acetylcarnitine, and spermidine and spermine, which were all involved in choline metabolism, carnitine metabolism, and polyamine metabolism. Our results suggested that GLP alleviated FA-exposed cognitive dysfunction, likely through modulation of metabolic pathways, providing a potential therapeutic approach for FA-related cognitive dysfunction.